JURIDICIAL REVIEW ON THE IMPLEMENTATION OF INVESTIGATIONS BY CIVIL SERVANTS INVESTIGATIONS IN IMMIGRATION CIVIL SERVANTS IMMIGRATION OFFICE SPECIAL SOEKARNO-HATTA - Badai Yogaswara W. S. M; Muhammad Azzam Alfarizi; M. Judo Ramadhan Sumantri (Polteknik Imigrasi, 2019)
Departing from the increasingly widespread problem of People Smuggling, both in the form of organized and unorganized crime networks, both inter-state and domestic as a whole is a threat to the norms of life based on human rights. In this case the role of the immigration officer as the gatekeeper in the country's traffic in the case of people entering / leaving Indonesian territory, as in 2015, the People Smuggling case was successfully revealed by the Immigration Officer within the Soekarno-Hatta Airport Airport I, where immigration officers found three people women wearing fake passports who were about to leave for Kuala Lumpur with perpetrators Laila Yunita and Jamal Al Khatib. This writing aims to analyze the causes and effects of human smuggling, as well as examine the serious efforts made by PPNS in eradicating People Smuggling, especially in the case of People Smuggling committed by Laila Yunita and Jamal Al Khatib. The research uses a statutory approach, a conceptual approach and a case approach. So that with the case, it will be understood how important the value of legal human resources is in the scope of immigration in the context of national law development, as a breakthrough in competency development strategies